Comparative effects of the 5'-triphosphates of 9-beta-(2'-azido-2'-deoxy-D-arabinofuranosyl)adenine and 9-beta-D-arabinofuranosyladenine on DNA polymerases from L1210 leukemia cells. - Allaudeen, H S (1982)
9-beta-(2'-Azido-2'-deoxy-D-arabiofuranosyl)adenine (arazide) causes greater and significantly more persistent inhibition of [3H]-thymidine incorporation into the DNA of neoplastic cells than the related agent 9-beta-D-arabinofuranosyladenine (araA). To elucidate the mechanism(s) responsible, we compared the effects of arazide and araA 5'-triphosphates on DNA polymerases alpha and beta of L1210 leukemia cells. Both nucleoside triphosphate analogs inhibited DNA polymerase alpha activity by competing with dATP; only araATP was inhibitory to DNA polymerase beta. Arazide triphosphate was at least four times more active than araATP as an inhibitor of DNA polymerase alpha. Preincubation of DNA polymerase alpha with either agent did not result in enzyme inactivation. The results suggest that interference with DNA polymerase alpha activity by arazide triphosphate may be in part responsible for the inhibition of DNA synthesis produced by arazide in neoplastic cells.